Polyploid GWAS reveals the basis of molecular marker development for complex breeding traits including starch content in the storage roots of sweet potato - Haque, Emdadul; Shirasawa, Kenta; Suematsu, Keisuke; Tabuchi, Hiroaki; Isobe, Sachiko; Tanaka, Masaru (Frontiers in Plant Science, 2023)
Given the importance of prioritizing genome-based breeding of sweet potato to enable the promotion of food and nutritional security for future human societies, here, we aimed to dissect the genetic basis of storage root starch content (SC) when associated with a complex set of breeding traits including dry matter (DM) rate, storage root fresh weight (SRFW), and anthocyanin (AN) content in a mapping population containing purple-fleshed sweet potato. A polyploid genome-wide association study (GWAS) was extensively exploited using 90,222 single-nucleotide polymorphisms (SNPs) obtained from a bi-parental 204 F1 population between ‘Konaishin’ (having high SC but no AN) and ‘Akemurasaki’ (having high AN content but moderate SC). Through the comparison of polyploid GWAS on the whole set of the 204 F1, 93 high-AN-containing F1, and 111 low-AN-containing F1 populations, a total of two (consists of six SNPs), two (14 SNPs), four (eight SNPs), and nine (214 SNPs) significantly associated signals were identified for the variations of SC, DM, SRFW, and the relative AN content, respectively. Of them, a novel signal associated with SC, which was most consistent in 2019 and 2020 in both the 204 F1 and 111 low-AN-containing F1 populations, was identified in homologous group 15. The five SNP markers associated with homologous group 15 could affect SC improvement with a degree of positive effect (~4.33) and screen high-starch-containing lines with higher efficiency (~68%). In a database search of 62 genes involved in starch metabolism, five genes including enzyme genes granule-bound starch synthase I (IbGBSSI), α-amylase 1D, α-amylase 1E, and α-amylase 3, and one transporter gene ATP/ADP-transporter were located on homologous group 15. In an extensive qRT-PCR of these genes using the storage roots harvested at 2, 3, and 4 months after field transplantation in 2022, IbGBSSI, which encodes the starch synthase isozyme that catalyzes the biosynthesis of amylose molecule, was most consistently elevated during starch accumulation in sweet potato. These results would enhance our understanding of the underlying genetic basis of a complex set of breeding traits in the starchy roots of sweet potato, and the molecular information, particularly for SC, would be a potential platform for molecular marker development for this trait.